DESIGNING A BOAT HOTEL (BOTEL) FOR MARINE TOURISM ON TABUHAN ISLAND, BANYUWANGI REGENCY, EAST JAVA - H, Hasanudin; Nasirudin, Ahmad; Saputra, Aditya Dwi (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
Tabuhan Island is one of the tourist islands in Banyuwangi Regency, which in 2020 was proclaimed by the Banyuwangi Regency government to become an international tourist destination. One of the efforts needed to make an international-class destination is to complete tourist objects with good infrastructure. One of the infrastructures that need to be completed is resorts and hotels. Design of Boat Hotel Catamaran (Botel Catamaran) is innovated with facilities equivalent to a 3-star hotel following the Ministry of Tourism and Creative Economy standards. This selection uses general dimension design parameters, which are then used in extensive travel and Botel facilities. Based on the calculations, the converted resistance of the engine has met the required power of 156 Hp. In addition, the calculation of the displacement-weight difference also showed a result of <9%, meeting the small ship margin requirement. The trim calculation also met SOLAS regulations with a result of 0% LWl < trim < 0.5% LWl. The freeboard calculation also met NCVS regulations with a result of Fb<(H-T). The tonnage calculation showed GT<500 GT, allowing the application of NCVS regulations. Finally, the comfort calculation (MSI) met the applicable ISO regulations. With these standardized calculation results, the engine is expected to operate optimally and safely. It was found that this ship has the final main dimensions, namely LoA = 29.26 m; Lpp = 28 m; B = 11.5 m; Height = 4 m; T=1.1m; B1 = 2.77; S = 6 m2 with a total of 6 rooms with a size of 30 m2 each and has been equipped with a restaurant and lounge. Then, the outline plan, general plan, and 3D model are drawn.